What is trending in libraries from the internet cybersphere. Issue 2 (2014) - Adetoun A. Oyelude
<x xml:space="preserve"> Abstract </x> Purpose – The paper aims to review what is trending on the internet and presents vignettes of related library technology and hot topics from weblogs, webinars, tweets, wikis and other discussions on the internet. Design/methodology/approach – A surfing of web sites, tweets, webinars, wikis and internet‐based information sites is done over a three‐month period and the trends identified and highlighted. Findings – The trends in various information and library‐related issues discussed online show a tending towards using new technology and the disadvantages of some, while advocating for review of some instructional methods by librarians to their clientele. Originality/value – The most current trends of discussion on the internet are presented up to the January 31, 2014.